Alokasi Belanja Sosial Pemerintah Daerah Terhadap Inklusi Sosial Kelompok Masyarakat Rentan Di Kota Parepare: Local Government Social Expenditure Allocation on Social Inclusion of Vulnerable Community Groups in Parepare City - Jumriani Arsyad; Fitriyani Syukri (Universitas Sulawesi Barat, 2025)
ABSTRACT Social inclusion has become a primary focus in local government budget planning as an effort to ensure equitable access for vulnerable groups. In Parepare City, the allocation of social spending in the regional budget (APBD) has been proven to have a positive and significant relationship with the increase in social inclusion levels, supported by data and regression analysis showing a correlation coefficient of 0.582 and a determination coefficient of 0.339. This study examines the impact of social spending on the social inclusion of vulnerable groups such as women, children, and persons with disabilities, highlighting the importance of quality management and community participation in the implementation of social programs. The study was conducted using a quantitative approach with data from the Social Service and the 2024 APBD documents of Parepare City, involving descriptive statistical and regression analyses. The results show that although social budget allocation significantly contributes to social inclusion, about 66% of the variation in social inclusion is influenced by other factors such as program governance and the effectiveness of aid distribution. Government policies that allocate a minimum of 15% of the budget for empowering vulnerable groups and the establishment of inclusive villages are concrete examples of efforts to improve social inclusion. However, these findings emphasize the need for improvements in management and implementation aspects to ensure that the benefits of social spending can be optimally realized. This study recommends that the Parepare City Government continue to enhance both the quantity and quality of social spending management to achieve inclusive and sustainable social development. Keywords: social spending, social inclusion, vulnerable groups, budget management, social programs